Contribution of age-related effects to differences in crude fatality ratios due to COVID-19 in two Argentine provinces between March and August 2020 - Octavio Nicolas Bramajo; Maria Florencia Bathory (Cadernos de Saúde Coletiva)
Abstract Background: The ongoing COVID-19 pandemic has affected Argentina with uneven intensity. The force of the mortality attributed to COVID-19 may vary across populations by age structure, which has to be considered when analyzing the impact of the pandemic. Objective: This paper presents net estimations of case fatality ratio (CFR) attributed to COVID-19 for two provinces in Argentina (Jujuy and Buenos Aires), using public data provided by the Argentine Ministry of Health. Method: After some sensitivity analyses, we opted to make a comparison between two given jurisdictions, Buenos Aires and Jujuy, by applying the Kitagawa decomposition procedure, separating rate ("net" fatality) and structure components (age-attributable effects) from CFR estimations in those provinces along standardized rates. Results: After the decomposition we observed that, while overall CFR differences between provinces are slight on average, the magnitude of structure and rate effects tends to go into different directions across age groups, indicating more premature mortality in Jujuy due to COVID-19. Conclusions: While comparing the CFR across populations may be a difficult task, we found a great deal of heterogeneity that exists across age groups when comparing two given fatality ratios.